A organização da informação arquivística: um modelo de aferição do nível de maturidade em gestão de documentos na era digital - Luis Pereira dos Santos; Renato Tarciso Barbosa de Sousa (Em Questão)
The organization of archival information in the digital age requires specific procedures; either because of the advent of digital archival records, or because the object of study has changed from sets of records to sets of organic information and archivology is witnessing new theoretical-methodological interlocutions with different disciplines that also have information as their object, such as Information Science. In the light of these developments, this research is based on the problem of analyzing how the management of digital archival documents can be measured at levels within document-producing organizations. To this end, this article presents a model for measuring maturity in the management of archival documents produced and kept in digital format. Objective: to propose a model for measuring the level of maturity in document management based on a study of existing models. Methodology: qualitative, documentary and bibliographical research. Results: by applying the new model for measuring the level of maturity in document management, it is possible to understand that the proposal is valid for measuring the level of maturity in document management in producing institutions. Conclusions: This research has shown that the record management maturity measurement model is valid and can be applied to any public institution in the digital information age to certify the quality of the custodian’s archival record management.